Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1055/s-0040-1714290
|View full text |Cite
|
Sign up to set email alerts
|

The Chimeric Propeller Flap

Abstract: A chimeric flap consists of multiple discrete tissues or flaps connected only by a common source vessel. Each component must have an independent source of circulation. Rotation of any included part only about its specific vascular supply, such as done with a propeller flap, would be possible. These characteristics, whereby the chimeric flap concept and propeller flap concept are combined, would result in a chimeric propeller flap. Such a choice will enhance overall flap insetting capabilities and versatility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…19 The chimeric propeller flap is a subtype of the compound flap that contains 2 or more independent components based on a common source vessel. 12 Rozen et al 20 reported the use of a chimeric dorsal scapular artery perforator flap combined with a trapezius muscle flap in obliterating dead space around an exposed cervicothoracic spinal prosthesis after the resection of metastatic renal cell carcinoma. This study confirmed that the chimeric flap could effectively cover the exposed prosthesis and obliterate the dead space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The chimeric propeller flap is a subtype of the compound flap that contains 2 or more independent components based on a common source vessel. 12 Rozen et al 20 reported the use of a chimeric dorsal scapular artery perforator flap combined with a trapezius muscle flap in obliterating dead space around an exposed cervicothoracic spinal prosthesis after the resection of metastatic renal cell carcinoma. This study confirmed that the chimeric flap could effectively cover the exposed prosthesis and obliterate the dead space.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge in reconstructing this type of wound is the 3-dimensional requirement of the flap, which covers the large skin defect and obliterates the dead space in a 1-stage procedure 19 . The chimeric propeller flap is a subtype of the compound flap that contains 2 or more independent components based on a common source vessel 12 . Rozen et al 20 reported the use of a chimeric dorsal scapular artery perforator flap combined with a trapezius muscle flap in obliterating dead space around an exposed cervicothoracic spinal prosthesis after the resection of metastatic renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…An even simpler chimeric flap alternative would be the traditional transfer of a medial gastrocnemius musculocutaneous flap, where the skin paddle were isolated on its perforator enough only to allow its rotation in any direction so as to better fit a given skin defect, as Innocenti et al 82 have done for knee defects. Some would call this variation a “chimeric propeller flap.” 83 …”
Section: Technical Variationsmentioning
confidence: 99%
“…Actually, if the dissection of the perforator into the muscle is minimal, that perforator flap so created can be rotated about that perforator to realign the orientation of the skin paddle of what was originally a composite musculocutaneous flap, making this yet another spinoff as a chimeric perforator pedicled propeller flap. 47 Some would argue that if multiple perforators exist within the angiosome of a given skin territory, the perforasome of each could be separated independently from the others to remain attached only where their specific perforator joins their common source vessel to form an indigenous chimeric perforator-based flap (Fig. 10).…”
Section: Chimeric Perforator Flapmentioning
confidence: 99%
“…Actually, if the dissection of the perforator into the muscle is minimal, that perforator flap so created can be rotated about that perforator to realign the orientation of the skin paddle of what was originally a composite musculocutaneous flap, making this yet another spinoff as a chimeric perforator pedicled propeller flap. 47…”
Section: Perforator Spinoffs: a Baker’s Dozenmentioning
confidence: 99%